Factors Associated With Non-Adherence to HAART amongst Adolescents Aged Between 18 and 25 Years Attending Parirenyatwa Opportunistic Infections Clinic, Zimbabwe - Sandra Makore; Mugadza, Gladys; Christine Mary Kasu, (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2020)
Successful Highly Active Antiretroviral Therapy was shown to rely on high levels of medication adherence to enable maximum and durable viral suppression, however adolescents face unique challenges in maintaining adherence. The purpose of the study was to determine the factors associated with non-adherence to Highly Active Antiretroviral Therapy amongst adolescents aged between 18 and 25 years attending Parirenyatwa Opportunistic Infections Clinic, Zimbabwe. Materials and Methods: A cross-sectional descriptive study design was conducted on 30 participants who met the inclusion criteria and the sample size was determined by convenient sampling method. Data was collected using a structured questionnaire while analysis utilized the computerized Statistical Package for Social Sciences Version 20.0 to yield descriptive statistics. Results: Results showed that fear of stigma and discrimination, disclosure, transport problems to health facility, bad attitude and communication of health workers, side effects, regime fatigue, lack of motivation and alcohol and substance use were associated with nonadherence to antiretroviral therapy. Discussion: These findings suggest overall that adolescents are facing great adherence challenges related to these common factors. The results yielded that interventions focusing on these factors might improve the adherence rate of adolescents to Highly Active Antiretroviral Therapy. Further qualitative research design should be carried out to investigate more on these factors Conclusion and Recommendation: Barriers of nonadherence among study participants included lack of social support, fear of stigma, disclosure, alcohol and substance use, feeling well, bad attitude and communication, difficulty in finding transport, drug side effects and regime fatigue were factors associated with nonadherence. There is need for the health workers to address such barriers for optimum adherence to Highly Active Antiretroviral Therapy.